Atwood’s Body Politic: a Taxonomy of Gender Representation (Philologia, 2021)
This article applies Butler’s concepts of gender as construction and performance to a selection of fiction by margaret Atwood. By using binary categories inspired by the theory of Eagleton and cixous, the author proposes a taxonomy of narrative techniques employed by Atwood to embed the female body into cultural and political discourse.
Keywords: Margaret Atwood; gender; female body in fiction